2021
DOI: 10.1111/ssqu.13046
|View full text |Cite
|
Sign up to set email alerts
|

Educational gender inequality in the Muslim world: A problem of a cultural heritage, religion, or modernization?

Abstract: The difference between the Muslim and non-Muslim world in terms of educational gender equality has been blamed on the Islamic faith, and sometimes on a lack of modernization. Thus, I examine how Islam reduces educational gender equality and how/if its influence varies from one Muslim country to another.Method: I use Time-series-cross-section (TSCS) analysis for 29 Muslim countries between 1980 and 2010 to examine the influence of Arab culture on educational gender parity. Result: The result indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Indicating that sociocognitive empowerment may empower women to deviate from extremist religious interpretations 35. Furthermore, countries with more conservative Muslim societies often display less openness to the impacts of modernisation 52. Considering that there is a larger educational gender gap among Muslims compared with followers of other religions,52 highly empowered Muslims likely represent a specific group characterised by exceptional education levels and a greater willingness to embrace new ideas and technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indicating that sociocognitive empowerment may empower women to deviate from extremist religious interpretations 35. Furthermore, countries with more conservative Muslim societies often display less openness to the impacts of modernisation 52. Considering that there is a larger educational gender gap among Muslims compared with followers of other religions,52 highly empowered Muslims likely represent a specific group characterised by exceptional education levels and a greater willingness to embrace new ideas and technologies.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, countries with more conservative Muslim societies often display less openness to the impacts of modernisation. 52 Considering that there is a larger educational gender gap among Muslims compared with followers of other religions, 52 highly empowered Muslims likely represent a specific group characterised by exceptional education levels and a greater willingness to embrace new ideas and technologies. Further exploration is required to better understand the pathways through which women's empowerment operates within Muslim communities.…”
Section: Global Healthmentioning
confidence: 99%
“…Our findings indicate that the effects of women's empowerment on DFPS were significantly higher among Muslims, with highly empowered Muslims showing the highest levels of DFPS. Studies have consistently found a larger educational gender gap among Muslims compared to followers of other religions (48). Furthermore, countries with more conservative Muslim societies often display less openness to the impacts of modernization (48).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently found a larger educational gender gap among Muslims compared to followers of other religions (48). Furthermore, countries with more conservative Muslim societies often display less openness to the impacts of modernization (48). Highly empowered Muslims likely represent a specific group characterized by exceptional education levels and a greater willingness to embrace new ideas and technologies.…”
Section: Discussionmentioning
confidence: 99%